A weberian look at the legitimacy deficit of the european union - Köse, Melike Akkaraca (My University, 2007)
Bu çalısma modernite ve liberalizmi Weber teorisi çerçevesinde ele alarak bulgularını ulusüstü bir otoritenin mesruiyet arayısına uygulamaya çalısır. Temel iddia, modernitenin ötesine geçen bir çok özelligi içinde barındırsa bile Avrupa Birlgi’nin hala Max Weber tarafından ayrıntılarıyla gösterilen modernitenin ikilemlerinin etkisi altında oldugu ve mesruiyet açıgının bu çeliskili çerçevede degerlendirilmesi gerektigidir. Bu perspektif bize çagımızda ve özelikle Avrupa Birligi’nde iktidar ve süje arasındaki tahakküm iliskilerinin çok fazla degismedigini hatta sıradan insan aleyhine ve iktidar lehine gelistigini göstermektedir; ulus-üstü iktidar kompleks ve anarsik dogasına ragmen ve hatta bazı durumlarda bu dogası nedeniyle güçlenmektedir. Max Weber, mesruiyet, Avrupa Birligi

The work focuses on Weberian theoretical approach to modernity and liberalism and applies its findings to the quest of a supranational order for legitimacy. Its main claim is that the Union, despite to the fact that it shows many characteristics of an entity beyond modernity, still suffers from the dilemmas of modernity and liberalism which have extensively been shown by Max Weber and its legitimacy deficit is to be evaluated in that dilemmatic context. This perspective shows us that the domination relation between authority and subject has not changed much but only developed more in favor of authority and at the expense of layman at our age and especially in the context of the European Union; this is so despite to, in some cases due to, complex and anarchic nature of the supra-national politics. Max Weber, legitimacy, European Union
Keywords: Avrupa Birliği_Hukuk; Meşruiyet